Poluição e impacto ambiental nos ecossistemas por meio de histórias em quadrinhos autorais: uma abordagem investigativa e crítica no município de Itabaiana – PB - Brito, Tiago Alves de (2022)
This work emerged from the observation and reflection of my teaching practice in teaching situations, where the methodologies adopted did not promote student protagonism. In this way, the need to analyze and re-signify the relationship between human beings and the environment was perceived, in view of the environmental impacts caused by human activities. Thus, an Investigative Teaching Sequence was developed and implemented with the objective of building scientific knowledge with basic education students about pollution and anthropic environmental impacts on ecosystems in the municipality of Itabaiana - PB, using assumptions of science teaching by investigation and of Critical Environmental Education, using the creation of comics as a didactic-methodological strategy. The methodological approach is characterized as qualitative research, which it will make use of theoretical-methodological assumptions of action research elements. The target audience was 42 students from E.E.E.F.M. João Fagundes de Oliveira, in remote teaching a group of 12 students and 30 students face-to-face teaching, all from the 1st grade of high school. The first stage was to apply a questionnaire with the objective of diagnosing the students' perceptions about the environment, environmental impact and Environmental Education. Then, the activities planned in the Investigative Teaching Sequence were developed, characterized by research, construction, hypotheses validation and presentation, with application of knowledge in workshops to make Comics related to the study themes of each group. Finally, the author's Comics were analyzed in the light of political-pedagogical macrotrends of Brazilian environmental education according to Layrargues and Lima (2014). From the collection and analysis of data, the prevalence of the perception of the environment as a “biosphere” in the context of remote teaching and the environment as “nature” for face-to-face teaching was observed. In the context of environmental impacts, in general students were identified human activities as promoters of environmental imbalance and pollution, highlighting that the human activities that cause the most environmental impact in the students' perception are: deforestation, solid waste and domestic effluents. In the analysis of the perception of Environmental Education, the most frequent categories in remote teaching were "Generalist" and "Socio-environmental-Cultural" and the predominant category of Environmental Education in classroom teaching was "Conservationist", that is, this perception is related to the practices committed to the rational use of natural resources, without considering the socio-cultural developments and their relationship with the environment, a perception that may be related to EE practices related to conservative and/or pragmatic political-pedagogical currents. In this sense, studies are suggested to establish the relationship between EE pedagogical practices in formal education and advances or setbacks in student perception, especially regarding the relationship between human beings and nature. Evidence indicates that the methodology used in the identification of environmental impacts from the assumptions of critical EE and Science Teaching by Investigation promoted student protagonism with the construction and reconstruction of knowledge, providing opportunities for participants to develop and acquire skills and competences related to the methods of thinking and doing science. In general, there is a need for EE practices beyond the walls of the school, in order to contribute to the education of students not only to pass in college entrance exams and ENEM, but also to provide opportunities for the development of aspects related to the citizenship. Finally, it is expected that the educational product, the result of this research, will help teachers in the application and development of pedagogical practices related to EE from a critical perspective.